Synthesis of Transition Metal Dichalcogenides from Solid-Phase Precursors - MC MANUS, JOHN BRENDAN (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2019)
Interest in telluride tranisition metal dichalcogenides (TMDs) has until very recently, lagged far behind that of more common TMDs such as MoS2. There are a number of potential reasons for this, such as these materials not being earth-abundant and being more challenging synthesise. Recent works however have examined telluride TMDs for use in thermoelectrics, spintronics, as Dirac and Weyl semimetals and have demonstrated topological insulating states. Nevertheless, the majority of works focus on mechanically exfoliated flakes, an inherently unscalable production method. This makes further works to examine the open challenge of scalable telluride TMD growth a worthwhile endeavour. This thesis examines the growth of a number of telluride containing TMDs, namely 1T' MoTe2, WTe2 and PtTe2. Films of each are grown by reacting transition metal films with electrodeposited Te in an inert furnace environment. The decision to electrodeposit solid Te onto the substrate prior to growth provided high concentrations of Te in direct contact with the metal film during growth, while avoiding the need for large amounts of vapour phase Te in the furnace. The successful growth of each material, at temperatures as low as 450 C, was verified by a range of spectroscopic techniques. Each was confirmed to be a phase-pure, polycrystalline film with some level of surface oxidation. Morphological characterisation indicated that the films consisted of crystal grains ranging from a few hundrad nanometres to 10 micrometres. Due to both the Pt and Te dewetting from the surface during the growth, the PtTe2 films often did not cover the whole surface and the crystals were found to be less 2D in nature do to strong interlayer bonds. The films were examined for use as electrocatlysts of the hydrogen evolution reaction (HER) and oxygen reduction reaction (ORR). While WTe2 did not show strong electrocatalytic behaviour, MoTe2 showed promising results with thicker films being more active. PtTe2 showed very strong activity for both HER and ORR, however some question marks remain over the results due to the dramatically different stoichiometry measured after the ORR measurements. This work demonstrates the production large-area, polycrystalline films of telluride TMDs. The electrodeposition of Te allowed high, localised concentrations of Te to directly react with the transition metal to form these films. The relatively low temperature of the growth opens up the opportunity for these films to be integrated with a wider range of processes than previously reported growth methods.
APPROVED
Keywords: layered material; electrodeposition; transition metal dichalcogenide; MoTe2; WTe2; PtTe2; hydrogen evolution reaction; electrocatalysis; thin-film